The Role of Accounting Literacy in Improving the Financial Performance of SMEs: A Study on Micro Entrepreneur Community in Indonesia - Nurani, N.; Intan Permatasari, Rr Lilis; Khalik, Abdul; Hamzah, Mukhtar; Nurhani, N. (Golden Ratio of Community Services and Dedication, 2025)
This study aims to examine the role of accounting literacy in improving the financial performance of micro, small, and medium enterprises (MSMEs), with a particular focus on micro-entrepreneur communities in Indonesia. Adopting a qualitative literature-based approach, the research synthesizes findings from forty-two peer-reviewed studies published between 2014 and 2025. The study explores how accounting knowledge, skills, and behavior collectively influence financial decision-making, liquidity management, profitability, and access to credit among micro-scale enterprises. Methodologically, a thematic synthesis was conducted based on a systematic literature search, quality appraisal using CASP and JBI frameworks, and coding through NVivo. Key findings reveal that accounting literacy is positively associated with critical financial indicators such as net profit margin, current ratio, and loan approval rates. Moreover, accounting literacy enhances the utility of digital bookkeeping applications and acts as a mediator in the effective adoption of financial technologies. In addition, the research identifies accounting literacy as a foundational capability for sustainability-related practices, including cost tracking for environmental impact, waste reduction, and access to green finance. These insights validate the conceptual framing drawn from human capital theory, the resource-based view, and absorptive capacity literature, positioning accounting literacy as a technical competency and a strategic resource for long-term enterprise resilience. The study concludes that accounting literacy is essential for inclusive economic development and recommends integrating literacy training with digital tools and sustainability incentives to enhance the competitiveness and sustainability of Indonesian micro-enterprises.